Revitalisasi Prajurit Nyutra Keraton Yogyakarta dan Dampaknya terhadap Identitas Budaya dan Pariwisata Budaya - Lutfi Maulana Hakim; Viona Amelia (Journal of Education, Humaniora and Social Sciences (JEHSS), 2026)
This study aims to analyse the revitalisation process of the Nyutra Soldiers of the Yogyakarta Palace during the reign of Sri Sultan Hamengku Buwono X and its impact on strengthening cultural identity and the development of cultural tourism. The study focuses on the transformation of the Nyutra Soldiers from a military unit into a ceremonial institution, as well as their contemporary revitalisation within the palace context. This research employs a descriptive qualitative approach. Data were collected through non-participatory observations conducted during three royal ceremonies—Garebeg Mulud, Garebeg Syawal, and Garebeg Besar—over the 2024–2025 period. Additional data were obtained from literature review, documentation, and informal interviews with Nyutra Soldiers. The data were analysed qualitatively using source and method triangulation techniques. The findings reveal that the revitalisation of the Nyutra Soldiers is concretely manifested through the reinstatement of Abdi Dalem Mataya in carrying thowok weapons, adjustments of costumes to reflect historical forms (sleeveless attire), and the reactivation of marching movements incorporating dance elements as representations of philosophical military values. This revitalisation not only restores the historical and symbolic dimensions of the Nyutra Soldiers but also reinforces their role as a cultural identity of the Yogyakarta Palace, particularly in public rituals such as the Garebeg ceremonies. Furthermore, the presence of the Nyutra Soldiers in cultural processions contributes to cultural tourism by serving as a heritage-based attraction that enhances the destination’s appeal in a sustainable manner. This study contributes to the discourse on cultural revitalisation by highlighting the interconnection between safeguarding intangible cultural heritage and strengthening heritage tourism, particularly within the context of the palace as a living heritage institution.